AL-TA'BIR AL-ISTHILAHI WA ISTI'MALATUHU FI KITAB SILSILAH TA'LIM AL-LUGHAH AL-'ARABIYAH - Rahman, Faridah; Abd. Safa, Najmuddin (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
This article aims to discuss Arabic idioms and their use in Book “Silsilat Ta’lim al-Lughah al-‘Arabiyyah” with semantic analysis. The urgency of this study is to help Arabic learners and enthusiasts in analyzing the meaning of Arabic sentences and language style so that they can avoid mistakes in understanding and translating various kinds of Arabic idioms. This study was a literature review using a qualitative approach. Data collection was carried out using the scrutinized method and note-taking technique, which recorded several Arabic idioms contained in the book Silsilat Ta’lim al-Lughah al-‘Arabiyyah level three, then analyzed using semantic analysis. Based on our study, it was concluded that the forms of Arabic idioms in the book ‘Silsilah Ta’lim al-Lughah al-Arabiyyah’ level three contained 46 idioms. They consist of two types: First, Arabic idioms are composed of fi'l (verbs) and harf (letters); secondly, Arabic idioms are arranged of ism (noun) and ism (noun).